MENGENTASKAN KEMISKINAN RAKYAT ACEH DENGAN SYARI'AH - M. Shabri Abd. Majid (Sharia and Law Faculty, 2017)
This study discusses the concept of poverty from an Islamic perspective. It then attempts to propose a holictic strategy to alleviate poverty in Aceh within the Shari’ah framework. To eradicate poverty, inter alia, the Acehnese should constantly and steadfastly improve their devoutness to Allah SWT. Their daily activities must be always in harmony with the Divine injunctions, the Holy Qur’an and Hadith. The elite groups must compromise and do not monopolize power and wealth in Aceh. Developmental budget should be proportionately distributed among the people of Aceh. Just economic and democratic political systems which are free from corruption and malpractices must be upheld. The rich Acehnese must fulfil their rights to the poor by paying zakat (Islamic tax). That ruling government should not be oppressive; the political elites should not take a chance to reap their benefits in the political instability in Aceh. The peaceful Aceh should be preserved so that the continous efforts to alleviate poverty can be easily intensified.